Anti-Allergic Properties of Curine, a Bisbenzylisoquinoline Alkaloid - Jaime Ribeiro-Filho; Márcia Regina Piuvezam; Patrícia T. Bozza (Molecules, 2015)
Curine is a bisbenzylisoquinoline alkaloid isolated from Chondrodendron platyphyllum (Menispermaceae). Recent findings have shed light on the actions of curine in different models of allergy and inflammation. Here we review the properties and mechanisms of action of curine focusing on its anti-allergic effects. Curine pre-treatment significantly inhibited the scratching behavior, paw edema and systemic anaphylaxis induced by either ovalbumin (OVA) in sensitized animals or compound 48/80, through mechanisms of mast cell stabilization and inhibition of mast cell activation to generate lipid mediators. In addition, oral administration of curine significantly inhibited eosinophil recruitment and activation, as well as, OVA-induced airway hyper-responsiveness in a mouse model of asthma, through inhibition of the production of IL-13 and eotaxin, and of Ca2+ influx. In conclusion, curine exhibit anti-allergic effects in models of lung, skin and systemic allergy in the absence of significant toxicity, and as such has the potential for anti-allergic drug development.